Intelligent Class Program Management (CI) Al Azhar Syifa Budi a Legend In Bekasi - Qathrunnada Qathrunnada; Noviyanto Noviyanto (Return : Study of Management, Economic and Bussines, 2022)
Background: Constitution Number 20 Years 2003 about The National Education System in article 5 paragraph (4) states that : " citizens who have potency intelligence and talent special entitled get education special ". The need attention special to participant students who have intelligence special and talent special is part function main education , namely develop potency participant educate by intact and optimal. Destination study this for could serve potency Participant Educate Intelligent Special need organized a service program special . The program must made with earnest and good governance ( management ) . Aim: Study this aim for look for information about CI class program management at SD Azhar Syifa Budi Legend. Method study qualitative descriptive for used in study this . Method: Data obtained through, observation , interviews and documentation, the main source of data school, insurer responsible for the program, teachers and parents CI students and documents related, data analysis with method make abstraction , categorized in check its validity . Findings: Results obtained from study this CI class program management at Al Azhar SD Elementary School Syifa Budi Legend includes activities ; planning , implementation and monitoring walk with good / effective with indicator implementation of the CI class program management process